Abdominal Cocoon Syndrome: Two Cases of an Anatomical Abnormality. (3rd April 2019) - Sovatzidis, Apostolos; Nikolaidou, Eirini; Katsourakis, Anastasios; Chatzis, Iosif; Noussios, George
Abstract : Introduction . Idiopathic sclerosing encapsulating peritonitis or abdominal cocoon syndrome (ACS) is a rare anatomical deformity characterized by the partial or complete encasement of the small intestine with fibrotic peritoneum. 193 cases have been described worldwide. The aim of this study is to present two cases of ACS successfully treated at the Surgical Clinic of the Agios Dimitrios General Hospital in Thessaloniki, Greece. Presentation of Cases . Two men (55 and 54 years old) presented to the emergency department complaining of abdominal pain, distension, constipation, nausea, and vomiting. Neither of these patients had any previous operations. The computed tomography scan of the first patient showed considerable distension of the small bowel, suggestive of internal herniation. The second case showed distention of the jejunum with no obvious cause. Both patients underwent emergency surgery. Intraoperatively, it was found that a fibrous membrane had completely covered the small intestine of the first patient and the jejunum and part of the large intestine of the second patient. Adhesiolysis and partial excision of the membrane were performed in both cases. Discussion . ACS is a rare cause of small bowel obstruction. Although conservative management with immunosuppressants and steroids has been described, surgical treatment is the gold standard. Conclusion . Preoperative clinical suspicion of this disease can help determine the diagnosis and protect surgeons from intraoperative "surprises".